ANALISIS NILAI TAMBAH MANISAN CARICA PADA BERBAGAI KEMASAN DI CV. YFBM KECAMATAN MOJOTENGAH, KABUPATEN WONOSOBO - Dewanti Risa Utami; Budiyoko Budiyoko; Wahyu Adhi Saputro (Fakultas Pertanian Universitas Mataram, 2022)
This study aims to: 1) determine the amount of added value and profit levels obtained from carica candied products in various packages obtained by the company; and 2) the pattern of marketing channels for candied carica products at CV. YFBM. The research method used is the descriptive method and the Hayami method is an analytical tool to calculate the value added of carica candied products in different types of packaging. The add-value analysis is calculated using primary data obtained from interviews and direct observation of respondents, namely parts from CV.YFBM and agent/ritails. The results of this study indicate that the value added of carica candied in various packages provides a high value added ratio of above 40% in the 130gr mini packaging of 63,65%, 53,98% in the 240gr bowl packaging and 63,37% in packaging n pouch. The value added profit contribution to the company has a high value. There are two patterns of carica candied marketing channels in various packages, in marketing channels I for carica candied products from the producer (CV.YFBM) directly to consumers. In marketing channel II, carica candied products flow from CV.YFBM to agent/retails is in the hands of the end consumer